Green Marketing and Intention to Buy Green Product: Systematic Literature Review - Lestari, Sri; Bakhtiar, Arfan; Suliantoro, Hery (Universitas Ahmad Dahlan, 2023)
Society in the current period is facing various kinds of challenges and obstacles related to the acceleration of urbanization and industrialization. As for the problems at the moment, namely the health crisis and pollution that can threaten the present or future generations so that action is needed to ensure optimal living conditions, it is becoming increasingly important to understand green marketing and various other forms of support. Therefore, the aim of this research is to carry out a systematic review of the literature to identify several factors that influence green marketing. For this study, the method used was a Systematic Literature Review (SLR) which was carried out by following the procedure and followed by a meta-analysis to see the relevance of the published articles. This study uses VOSViewer as auxiliary software and uses Publish or Perish to help group data. From the search results, a total of 865 related articles were found for 2017-2022 and sorting was carried out to find relevant articles. The literature review was carried out using qualitative analysis, which resulted in four keywords; green marketing mix, attitude, purchase decision, and green marketing. In the end, we propose a framework that is developed based on some of the findings obtained. It is hoped that this framework can be used for a better understanding of green marketing factors that influence consumer purchase intentions.